Physical therapy at the stages of recovery after revision endoprothesis of the hip joint - Borys Pustovoit; Pavlo Yefimenko; Mykola Tokhtamyshev; Oksana Kanishcheva (Kharkiv State Academy of Physical Culture, 2021)
Purpose: scientific substantiation, development and evaluation of the effectiveness of the program of physical therapy of patients in the revision endoprothesis of the hip joint. Material and methods: analysis of literary sources, indicators of blood pressure and pulse, anthropometry, goniometry, testing on the SCALE of VAS, mathematical statistics. The contingent of the studied was compiled by patients of the State Institution "Institute of Spine and Joint Pathology named after Prof. M.I.Sitenko AMNU in the number of 19 people divided into 2 groups, the main - 10 and control - 9. The duration of the developed intensive PT program for patients of the main group is 37 days, 10 days, the preoperative period - before surgery and 27 days after (early postoperative - 5 days, late postoperative - 7 days, early recovery - 15 days). Patients of the control group at the same time underwent a rehabilitation course according to the generally accepted method. Results: dynamics, blood pressure and pulse indicators, anthropometry, goniometry of the hip and knee joints, intensity of pain syndrome on the SCALE of VAS, determined that all the indicated indicators were statistically better in patients of the main group. Conclusions: during revision endoprosthesis, the patient's body should be prepared to prevent postoperative complications with the help of means and methods of physical therapy; patients of both groups had improved indicators of cardiovascular hemodynamics, indicators of dynamics of braided hip size, volume of movements in the hip and knee joints, testing the intensity of pain on the SCALE of VAS. However, in patients of the main group, in comparison with patients of the control group, a significant (statistically proven) improvement of all indicators was found; observations confirmed that segmental-reflex massage can be carried out in the early stages of rehabilitation; the studies obtained in dynamics make it possible to affirm that we have proven the high efficiency of the developed program of physical therapy of patients in the revision endoprothesis of the hip joint, which allows us to significantly improve the condition of the musculoskeletal system and the body as a whole.